Parents' Attention To Children's Learning Increases The Competence Of Children's Learning Outcomes During The Pandemic 19 - Mona Fitri Gurusinga; Afrilius Simanjuntak; Hera Wati Bukit; Hengki Frengki Manullang (INSTITUT KESEHATAN DELI HUSADA, 2023)
The aim of this research is to describe: (1) To find out how the role of parents influences efforts to increase the competence of children's learning outcomes during the Covid-19 pandemic, (2) The obstacles experienced by parents in efforts to increase the competence of children's learning outcomes during the pandemic covid-19. This research is described as qualitative research with data collection through questionnaires and interviews. which delved deeper between researchers and informants to obtain specific data and also used other data collection techniques that were supported to obtain information, namely, the technical tools of the use of cameras and voice recorders, as well as the use of literary studies. The results of this research show that the role of